Modified zein delivery carrier as well as preparation method and application thereof

By using Na2CO3 solution or Na2CO3 sacrificial template solution on zein nanoparticles and undergoing phosphorylation modification, the problem of insufficient solubility, stability and dispersion of zein delivery vector is solved, and its performance as a delivery vehicle is significantly improved.

CN119499392AActive Publication Date: 2025-02-25YANGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411635132.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Zeinol itself has poor solubility, stability and dispersion, resulting in poor performance as a delivery vehicle.

Method used

Zein nanoparticles were prepared by using Na2CO3 solution or Na2CO3 sacrificial template solution and phosphorylated to form a modified zein delivery vector.

Benefits of technology

The solubility, storage stability, emulsification, foaming and encapsulation properties of modified zein nanoparticles have been significantly improved, and the performance as a delivery carrier has been greatly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499392A_ABST
    Figure CN119499392A_ABST
Patent Text Reader

Abstract

The invention discloses a modified zein delivery carrier as well as a preparation method and application thereof. The modified zein delivery carrier is obtained by preparing zein nanoparticles with solid structures or hollow structures from a Na2CO3 solution or a Na2CO3 sacrificial template solution and then performing phosphorylation modification. Compared with nano-particles prepared from unmodified zein, the phosphorylated zein nano-particles have the advantages that the solubility is better, the storage stability is higher, the emulsifying property, the foaming property and the encapsulating property are remarkably improved, and the performance of the phosphorylated zein nano-particles serving as a delivery carrier is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified zein delivery carrier and a preparation method and application thereof, belonging to the field of delivery carriers. Background Art

[0002] Zein is mainly derived from corn endosperm and is a common natural plant-based biopolymer. However, the high level of α-helix displayed in the three-dimensional structure of zein gives it a unique self-assembly property, making it an ideal material for delivering bioactive substances, especially hydrophobic bioactive substances. Zein-based delivery systems can be mainly divided into two categories according to the size of droplets or particles: micron-scale (such as microparticles, microcapsules, Pickering emulsions, etc.) and nanoscale (nanoparticles, nanofiber films, nanoemulsions, etc.). Among them, nanoparticles have become a commonly used delivery system due to their simple manufacturing process and excellent oral availability. However, zein itself has poor solubility, stability and dispersibility, so it is necessary to modify zein or zein particles to obtain nanoparticles with excellent delivery effect. Summary of the invention

[0003] Purpose of the invention: The first purpose of the present invention is to provide a modified zein delivery carrier, the second purpose of the present invention is to provide a method for preparing the modified zein delivery carrier, and the third purpose of the present invention is to provide the application of the modified zein delivery carrier in the preparation of drugs or functional food ingredients.

[0004] Technical solution: A modified zein delivery vector of the present invention comprises zein nanoparticles prepared by using a Na2CO3 solution or a Na2CO3 sacrificial template solution and then modified by phosphorylation.

[0005] Furthermore, the zein nanoparticles are hollow structures or solid structures.

[0006] Furthermore, the phosphorylation modification is carried out by sodium tripolyphosphate.

[0007] Furthermore, the preparation of the Na2CO3 sacrificial template solution includes the following steps: mixing the Na2CO3 aqueous solution with anhydrous ethanol.

[0008] Furthermore, the concentration of the Na2CO3 aqueous solution is 0.5-2.5% (w / v).

[0009] Furthermore, the volume ratio of the Na2CO3 aqueous solution to anhydrous ethanol is 1-5:9-5.

[0010] The method for preparing the modified zein delivery carrier of the present invention comprises the following steps:

[0011] (1) Mixing a zein stock solution with a Na2CO3 sacrificial template solution and stirring to obtain a mixed solution. Mixing the mixed solution with ultrapure water, continuing to stir, and rotary evaporating to obtain hollow zein nanoparticles (HZn);

[0012] Alternatively, a zein stock solution is mixed with a Na2CO3 solution, stirred to obtain a mixed solution, the mixed solution is mixed with ultrapure water, stirred continuously, and rotary evaporated to obtain zein nanoparticles (SZn) with a solid structure;

[0013] (2) Mix the sodium tripolyphosphate solution with the hollow or solid zein nanoparticle solution and stir.

[0014] Furthermore, in step (1), the concentration of the zein stock solution is 0.5-2.5% (w / v), and the volume ratio of the zein stock solution to the Na2CO3 sacrificial template solution is 1:1-5.

[0015] Furthermore, in step (1), the stirring time is 2-10 min, and the volume ratio of the mixed liquid to ultrapure water is 1:1-5.

[0016] Furthermore, in step (1), the stirring time is continued for 10-30 min, the rotary evaporation temperature is 35-42° C., and the rotary evaporation time is 25-40 min.

[0017] Furthermore, in step (2), the mass ratio (w / w) of sodium tripolyphosphate to zein nanoparticles is 0.75-1.5:1.

[0018] The invention discloses an application of the modified zein delivery carrier in the preparation of medicine or functional food ingredients.

[0019] Furthermore, the drug or functional factor is puerarin.

[0020] Generally, phosphorylation-modified proteins refer to protein molecules that undergo phosphorylation modification on specific amino acid residues, that is, a phosphate group is added. This modification is usually catalyzed by kinases and is a reversible post-translational modification process that has an important impact on the function, activity, stability, and subcellular localization of proteins. Phosphorylated proteins are widely present in cells and involve various biological processes such as cell signaling, cell cycle regulation, and metabolic regulation. The phosphorylation-modified protein particles of the present invention are prepared into protein particles by first using a Na2CO3 or Na2CO3 sacrificial template with corn alcohol-soluble protein, and then phosphorylated, utilizing the special properties of nanoparticles (such as large specific surface area, special force, electricity, magnetism, light, and thermal properties) and the biological properties of phosphorylated proteins. By regulating the construction of nanoparticles and further phosphorylation modification conditions, a nano delivery carrier with excellent comprehensive performance is obtained. Protein particles modified by phosphorylation can not only improve the stability and bioavailability of hydrophobic drugs or functional factors, but also regulate the release kinetics of drugs by regulating the surface properties and sustained-release properties of nanoparticles, thereby playing an important role in drug delivery systems. Compared with phosphorylation-modified proteins, preparing particles first and then phosphorylating them mainly changes the surface modification sites, while some potential phosphorylation sites inside are less likely to be phosphorylated because they participate in the interaction between protein molecules in the particles. Therefore, a particle structure with a hydrophilic exterior and a hydrophobic interior can be formed, which is conducive to the encapsulation of hydrophobic active substances.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0022] The modified zein delivery carrier provided by the present invention is a phosphorylated zein nanoparticle. Compared with the zein nanoparticles prepared from unmodified zein, the modified zein nanoparticles have the advantages of better solubility, stronger storage stability, and significantly improved emulsification, foaming and encapsulation properties, which greatly improves its performance as a delivery carrier. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The phosphorylation degree diagram of PHZn and PSZn prepared in Example 1;

[0024] Figure 2 The particle size and potential diagrams of HZn solution, SZn solution, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 were prepared for Example 1;

[0025] Figure 3 The free amino content graph of HZn solution, SZn solution, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared for Example 1;

[0026] Figure 4 The free thiol content graph of HZn solution, SZn solution, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared for Example 1;

[0027] Figure 5 SEM images of HZn, SZn, PHZn1, and PSZn1 prepared in Example 1;

[0028] Figure 6 TEM images of HZn and SZn prepared in Example 1;

[0029] Figure 7 Infrared spectra of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared for Example 1;

[0030] Figure 8 Circular dichroism spectra of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 were prepared for Example 1;

[0031] Fig. 9 The fluorescence emission spectra of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1 and PSZn1 prepared in Example 1;

[0032] Fig.10 The protein solubility comparison chart of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared in Example 1;

[0033] Fig.11 The particle size change diagram of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 at different times prepared in Example 1;

[0034] Fig.12 The foaming result diagram of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1 and PSZn1 prepared in Example 1;

[0035] Fig.13 The emulsification results of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1 and PSZn1 prepared in Example 1 are shown in FIG.

[0036] Fig.14The encapsulation efficiency and loading rate diagram of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 encapsulating puerarin prepared in this example. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0038] Example 1

[0039] 1. Sample preparation

[0040] (1) Hollow zein nanoparticles (HZn) were prepared using Na2CO3 sacrificial template.

[0041] First, a 5% (w / v) zein stock solution was prepared with a freshly prepared 70% (v / v) ethanol solution, and a 1% (w / v) Na2CO3 aqueous solution was mixed with anhydrous ethanol at a ratio of 3:7 to prepare a Na2CO3 sacrificial template solution. Then, the 5% (w / v) zein stock solution was fully mixed with the Na2CO3 sacrificial template solution at a ratio of 1:1 and magnetically stirred for 5 min to obtain a mixed solution. Then, the mixture of the zein stock solution and the Na2CO3 sacrificial template solution was mixed with ultrapure water at a ratio of 1:4 (v / v) and magnetically stirred for 10 min to precipitate Na2CO3 and leave a cavity inside the zein nanoparticles. Finally, a rotary evaporator was used at 38°C for 35 min to remove the ethanol in the system, and ultrapure water was added to make up the evaporation volume to obtain a hollow structure zein nanoparticle (HZn) solution.

[0042] (2) The preparation process is the same as step (1), and the other sample preparation steps remain unchanged. The difference is that an equal amount of Na2CO3 aqueous solution is used to replace the Na2CO3 sacrificial template solution to prepare a solid structure zein nanoparticle (SZn) solution as a control.

[0043] (3) 5 mg, 12.5 mg, 25 mg, 27.5 mg, 50 mg, 62.5 mg and 75 mg of sodium tripolyphosphate (STP) were dissolved in 40 mL of ultrapure water to form STP solutions of different mass concentrations, and 10 mL of hollow zein nanoparticle solution or solid zein nanoparticle solution was mixed with it, and magnetic stirring was performed for 30 min to allow the phosphorylation reaction to be complete. At this time, the mass ratio (w / w) of STP to zein was 0.1, 0.25, 0.5, 0.75, 1, 1.25 and 1.5, respectively. After the phosphorylation reaction, the nanoparticle solution was divided into dialysis bags at 4°C and dialyzed with deionized water for 72 h. Finally, the dialyzed solution was freeze-dried to obtain powder samples, and phosphorylated hollow zein nanoparticles (PHZn) and phosphorylated solid zein nanoparticles (PSZn) were obtained, respectively, and sealed and placed in a 4°C refrigerator for use.

[0044] 2. Phosphorylation degree test

[0045] Take 5 mL of the sample of the phosphorylated hollow zein nanoparticles or the phosphorylated solid zein nanoparticles prepared in Example 1, add an excess of 10% triacetic acid (TCA) to precipitate the protein, centrifuge at 4000 r / min for 10 min, and take the supernatant. Then, add an excess of 1 mol / L zinc acetate solution to the supernatant to adjust the pH to 3.8 to form a precipitate, and then add ammonia-ammonium chloride buffer with a pH of 10 to dissolve it. Finally, use chrome black T as an indicator and titrate with 0.1 mol / L disodium ethylenediaminetetraacetic acid (EDTA-Na2) standard solution. The solution turns from purple-red to blue, stop the titration, and record the volume. The results are as follows: Figure 1 shown.

[0046] Figure 1 The comparison diagram of the phosphorylation degree of PHZn and PSZn prepared in Example 1 is shown in FIG. Figure 1It can be seen that the phosphorylation degree of PHZn and PSZn first increased and then decreased with the addition of STP, and the phosphorylation degree of PHZn was always higher than that of PSZn. When the value of STP / zein (w / w) was 1, the phosphorylation degree of the two phosphorylated zein nanoparticles reached the highest level, which was 50.79 mg / g and 48.83 mg / g, respectively. On this basis, samples with STP / zein (w / w) values ​​of 0.1, 0.5 and 1 were selected as low phosphorylation degree zein nanoparticles (PHZn0.1, PSZn0.1), medium phosphorylation degree zein nanoparticles (PHZn0.5, PSZn0.5), and high phosphorylation degree zein nanoparticles (PHZn1, PSZn1) for subsequent research. If phosphate is added in excess, it will lead to overphosphorylation of protein particles, increase electrostatic interactions between particles, and cause protein aggregation to form larger particles; excessive phosphorylation may cause irreversible changes in the structure of protein particles, thereby affecting their biological functions, such as enzyme activity and binding properties; excessive phosphate may cause excessive surface charge on nanoparticles, increase repulsion between particles, and affect their stability; in addition, in drug delivery systems, the stability and targeting of nanoparticles are crucial. Excessive phosphorylation modification may change the surface properties of nanoparticles and affect their interactions with biomolecules, thereby reducing the efficiency and targeting of drug delivery.

[0047] 3. Particle size and potential test

[0048] About 1.5 mL of HZn solution, SZn solution, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared in Example 1 were respectively taken and placed in a quartz dish for particle size analysis, and Zeta potential was measured using a potential cell. The results are shown in FIG. Figure 2 shown.

[0049] Figure 2 The particle size and potential comparison diagram of HZn solution, SZn solution, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared for Example 1, where A is the particle size and B is the potential. Figure 2It can be seen that with the increase of phosphate concentration, the particle size of PHZn and PSZn increased from 138.2nm and 170.5nm to 186.5nm and 222.4nm, respectively, and the particle size of HZn was always smaller than that of SZn. When STP was not added, the surfaces of HZn and SZn were negatively charged, and the zeta potentials were -27.7mV and -25.7mV, respectively. With the gradual addition of STP, the negatively charged phosphate groups gradually bound to the protein, and the electronegativity of PHZn and PSZn increased. When the mass ratio of STP to zein was 1, the zeta potential reached a maximum value of -53.2mV and -50.2mV, respectively, which was nearly twice that of the unphosphorylated sample. Before and after the phosphorylation reaction and in samples with different phosphorylation degrees, the absolute value of the measured Zeta potential value of HZn was greater than that of SZn.

[0050] 4. Determination of free amino groups

[0051] The free amino content of HZn solution, SZn solution, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1 and PSZn1 prepared in Example 1 was determined by the o-phthalaldehyde (OPA) method. Figure 3 shown.

[0052] Figure 3 A comparison chart of the free amino group contents of HZn solution, SZn solution, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared in Example 1; Figure 3 It can be seen that the initial values ​​of free amino groups of HZn and SZn were 0.202mmol / g and 0.193mmol / g, respectively, which decreased to 0.134mmol / g and 0.143mmol / g as the phosphorylation reaction proceeded, a decrease of 0.068mmol / g and 0.050mmol / g, respectively. When phosphorylation modification was not performed, the free amino group content of HZn was higher than that of SZn.

[0053] 5. Determination of free thiol groups

[0054] Dissolve 5,5'-dithiobis(2-nitrobenzoic acid) in Tris-Gly buffer (pH 8.0, containing 0.086mol / LTris, 0.09mol / L Gly, 0.004mol / L EDTA, 8mol / L Urea) to prepare Ellman's reagent at a concentration of 4mg / mL. Take 1mL of the sample solution and add it to 2mL of Tris-Gly buffer solution, and mix it with 100μL of Ellman's reagent. Incubate it at room temperature in the dark for 30min, and measure the absorbance at 412nm. Replace the sample solution with an equal amount of ultrapure water and mix it with 2mL of Tris-Gly buffer solution as a blank control. The above sample solutions are HZn solution, SZn solution, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared in Example 1, respectively, and the content of free thiol groups is measured respectively. The results are as shown in the figure. Figure 4 shown.

[0055] Figure 4 A comparison chart of free thiol contents of HZn solution, SZn solution, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared in Example 1; Figure 4 It can be seen that with the increase of phosphorylation degree, the free thiol contents of PHZn and PSZn showed a downward trend, decreasing by 14.36 μmol / g and 12.25 μmol / g, respectively.

[0056] 6. Scanning electron microscope test

[0057] Take appropriate amounts of freeze-dried samples HZn, SZn, PHZn1, and PSZn1 and place them on metal conductive planes and plate them with gold. Use S-4800Ⅱ field emission scanning electron microscope to observe the surface morphology of the samples at an accelerating voltage of 10.0 kV. The results are shown in Figure 5 shown. Figure 5 The SEM images of HZn, SZn, PHZn1 and PSZn1 prepared in Example 1 are shown in FIG. Figure 5 It can be seen from the result diagram of low magnification (magnification 1k) that all samples are in the state of lamellar aggregates; from the result diagram of high magnification (magnification 50k), it can be seen that the individual particles of all samples are spherical, and the average particle size is between 100-200nm, which is the same as the particle size measurement results. Compared with particles with solid structures, particles with hollow structures have smaller particle sizes (magnification 50k) and more uniform distribution (magnification 10k). When the phosphate group is inserted, the sample particles become uneven (magnification 50k), obvious small holes appear on the surface of the aggregates (magnification 1k), and a network structure is observed (magnification 10k). Transmission electron microscopy analysis was performed on the freeze-dried samples HZn and SZn, and the results are as follows. Figure 6shown. Figure 6 TEM images of HZn and SZn prepared in Example 1; Figure 6 It can be seen that the prepared HZn particles have a hollow structure, while the SZn particles have a solid structure.

[0058] 7. Fourier infrared test

[0059] The freeze-dried sample powders of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared in Example 1 were fully ground and mixed with dried potassium bromide powder in a ratio of 1:150, and then pressed into tablets and measured for infrared spectroscopy. The measurement parameters were set to scan range: 4000-400cm-1, resolution: 4cm-1, and scan times: 32 times. The results are as follows Figure 7 shown.

[0060] Figure 7 The infrared spectra of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1 and PSZn1 were prepared in Example 1; Figure 7 It can be seen that all samples have a -1 The absorption peak near 2960cm is mainly due to the stretching vibration of OH bound to hydroxyl and the asymmetric stretching vibration of NH. -1 The absorption peak near 1650cm is mainly due to the asymmetric stretching vibration of -CH2; -1 The absorption peak near 1540cm is mainly due to the stretching vibration of C=O; -1 The absorption peaks near are mainly due to the stretching vibration of CN and the bending vibration of NH. The new characteristic peaks shown by the phosphorylated zein nanoparticle sample at 1135cm-1, 990cm-1, and 895cm-1 belong to the stretching vibration of PO and P=O, indicating that the phosphate group has been successfully integrated into the protein side chain.

[0061] 8. Circular dichroism test

[0062] Take appropriate amount of deionized water to dilute the HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, PSZn1 solutions prepared in Example 1 to 0.2% (w / v), then add the diluted sample solutions into quartz micro-cuvettes and measure their spectra at 190-250nm by circular dichroism spectrometer. The results are as follows: Figure 8 shown.

[0063] Figure 8The circular dichroism spectra of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1 and PSZn1 were prepared for Example 1. Figure 8 It can be seen that all samples have two negative peaks at around 210nm and 225nm and a positive peak at around 195nm, which is a typical feature of zein rich in α-helical structure. At the same phosphorylation degree, the negative peak intensity of HZn is higher than that of SZn, indicating that the α-helix content in HZn is higher than that in SZn. With the continuous increase of the phosphorylation degree, the negative peak intensity of PHZn and PSZn increases to varying degrees, indicating that phosphorylation can increase the α-helix content of zein.

[0064] 9. Intrinsic fluorescence spectroscopy

[0065] The fluorescence emission spectra of the HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 samples prepared in Example 1 were measured using a fluorescence spectrophotometer. The sample concentration was fixed at 1 mg / mL, the excitation wavelength was set at 280 nm, the spectrum scanning range was 290-400 nm, and the excitation and emission slit widths were both 5 nm. The results are shown in Figure 2. Fig. 9 shown.

[0066] Fig. 9 The fluorescence emission spectra of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1 and PSZn1 prepared in Example 1 are shown in FIG. Fig. 9 It can be seen that the fluorescence intensity of both hollow and solid structure samples increases with the increase of STP concentration, and the fluorescence intensity of HZn is significantly higher than that of SZn.

[0067] 10. Solubility

[0068] The HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 protein samples prepared in Example 1 were diluted to 0.5 mg / mL with ultrapure water, and then centrifuged at 12000r for 3 min at room temperature. The supernatant was measured and the dissolved protein concentration was calculated using a BCA protein concentration kit. Natural zein was used as a control. The protein solubility was calculated according to the following formula:

[0069]

[0070] Where C1 is the measured supernatant protein concentration, and C0 is the diluted protein sample concentration: 0.5 mg / mL. Fig.10 shown.

[0071] Fig.10 The protein solubility comparison chart of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared in Example 1 is shown in FIG. Fig.10 It can be seen that the solubility of natural zein is only 4.61%, which greatly limits its application in the field of delivery carriers. When zein was prepared into solid and hollow structure particles, the solubility was increased to 21.88% and 26.08%, respectively. After phosphorylation modification with STP, the solubility of SZn and HZn was further improved, reaching the highest 36.34% and 43.45% when the amount of STP added was equal to the mass of zein. At the same degree of phosphorylation, the solubility of HZn was always higher than that of SZn. It is precisely because the physical and chemical indicators of HZn are better than those of SZn that the functional properties of HZn are ultimately better than those of SZn.

[0072] 11. Storage stability

[0073] The HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, PSZn10.1% (w / v) sample nanoparticle aqueous dispersion prepared in Example 1 was placed at room temperature for 21 days. The particle size of the sample was measured at 25°C using a Malvern Zetasizer ES90 Nano laser particle size analyzer on the 1st day, 7th day and 21st day, and the storage stability of the sample was analyzed by the change in the sample particle size. The results are shown in FIG. Fig.11 shown.

[0074] Fig.11 The particle size change diagrams of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1 and PSZn1 prepared in Example 1 at different times are shown in FIG. Fig.11 It can be seen that the particle size of all samples did not change significantly within 7 days, indicating that zein nanoparticles can maintain good stability within one week of storage at room temperature. After 21 days of storage, the particle size of HZn and SZn greatly expanded to 774.9nm and 872.4nm, respectively, which increased by 636.7nm and 701.9nm compared with the first day. The particle size change of the phosphorylated samples was significantly smaller than that of the unphosphorylated samples, and the higher the degree of phosphorylation, the smaller the particle size change.

[0075] 12. Foaming and foaming stability

[0076] 5 mL of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 solution samples prepared in Example 1 were placed in a centrifuge tube with a clear scale, and the total volume of the sample was recorded after shearing for 2 min at 10,000 rpm using a high-speed homogenizer, and then the total volume of the sample was recorded again after standing at room temperature for 30 min. The calculation formulas for FC and FS are as follows:

[0077]

[0078] Where V0 is the initial volume of the sample, V1 is the volume of the sample after high-speed shearing, and V2 is the volume of the sample after standing for 30 minutes. Fig.12 shown.

[0079] Fig.12 The steam drum result diagram of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1 and PSZn1 prepared in Example 1, where A is the foaming property and B is the bubble stability. Fig.12 It can be seen that the foaming properties and foaming stability of solid and hollow zein nanoparticles show an increasing trend with the deepening of phosphorylation degree, and the hollow structure particles are always slightly higher than the solid structure particles. The foaming property of SZn increased from 14.13% to 35.76%, and the foaming stability increased from 75.86% to 90.65%; the foaming property of HZn increased from 17.53% to 38.60%, and the foaming stability increased from 76.34% to 92.67%.

[0080] 13. Emulsification and emulsion stability

[0081] 15mL of the 0.1% (w / v) sample nanoparticle aqueous dispersion of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, PSZn1 prepared in Example 1 was fully mixed with 5mL of edible peanut oil, and then an emulsion was prepared by high-speed homogenizing emulsifier at a speed of 10000rpm for 4min. The prepared emulsion was allowed to stand for 20min, and 50μL of the emulsion was drawn from the bottom at 0min and 20min, respectively, and fully mixed with 5mL of 0.1% (w / v) sodium dodecyl sulfate (SDS) solution, and the absorbance was measured at 580nm. EAI and ESI were calculated according to the following formula.

[0082]

[0083] Where N represents the dilution factor; C represents the protein concentration before emulsification, g / mL; Ψ represents the volume fraction of the oil phase; A0 and A20 represent the absorbance of the dilution at 580nm at 0min and 20min, respectively. Fig.13 shown.

[0084] Fig.13 The emulsification results of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 prepared in Example 1 are shown in Figure 1, where A represents emulsification and B represents emulsification stability. Fig.13 It can be seen that with the increase of phosphorylation degree, the EAI and ESI of both hollow and solid structures increased significantly. The EAI of SZn and HZn increased from 19.25m2 / g and 25.09m2 / g before phosphorylation to 103.77m2 / g after phosphorylation. 2 / g and 137.88m 2 / g, both increased by more than 5 times; the ESI of SZn and HZn also increased from 19.2% and 25.09% before phosphorylation to 73.58% and 78.74% after phosphorylation, respectively.

[0085] 14. Encapsulation rate and loading rate

[0086] In order to explore the effect of phosphorylation modification on the encapsulation of hydrophobic active substances by nanoparticles, the encapsulation efficiency and loading rate of the sample were measured with puerarin as a representative. 10 mg of puerarin was weighed and added to 1 mL of 5% (w / v) zein stock solution and magnetically stirred for 15 min to replace the 5% (w / v) zein stock solution in Example 1. The remaining steps were prepared according to the sample preparation steps of Example 1 to prepare sample particles loaded with puerarin.

[0087] The content of puerarin encapsulated in the nanoparticles was determined by UV-visible spectrophotometry. The sample was centrifuged at 2000r for 20min to remove unstable large particles and unencapsulated puerarin. 300μL of supernatant was added to 700μL of anhydrous ethanol and appropriately diluted with 70% ethanol. The absorbance of the sample dilution at 250nm was then determined by a UV spectrophotometer. The absorbance value obtained was substituted into the puerarin standard curve: y=0.1123x+0.0206 to calculate the content of successfully encapsulated puerarin. In the formula, y represents the absorbance value and x represents the puerarin concentration (μg / mL). The encapsulation efficiency (EE) and loading capacity (LC) of puerarin were calculated according to the following formula:

[0088]

[0089] Among them, M2 is the content of embedded puerarin (mg), M1 is the initial addition amount of puerarin (mg), and M0 is the mass of zein (mg). The results are as follows Fig.14 shown.

[0090] Fig.14 The encapsulation efficiency and liability ratio of HZn, SZn, PHZn0.1, PSZn0.1, PHZn0.5, PSZn0.5, PHZn1, and PSZn1 encapsulating puerarin prepared in this example are shown in Figure 1, where A is the encapsulation efficiency and B is the liability ratio. Fig.14 It can be seen that using puerarin as a model, the effects of Na2CO3 template method for preparing hollow particles and STP-induced phosphorylation modification on the EE and LC of zein nanoparticles were investigated. Fig.14 As shown. Fig.14 It can be seen that compared with SZn, the EE of HZn increased from 60.24% to 69.39%, and the LC increased from 12.05% to 13.88%, both of which were significantly improved. This is due to the larger surface area provided by the preparation of hollow particles and the cavity formed after the diffusion of Na2CO3, which left more capture sites for bioactive substances, thereby improving the encapsulation efficiency and loading capacity of puerarin. After STP-induced phosphorylation, the EE and LC of SZn and HZn both increased steadily with the increase in the degree of phosphorylation, which was attributed to the phosphorylation modification that exposed the hydrophobic groups inside the protein and increased the surface hydrophobicity of zein.

Claims

1. A modified zein delivery carrier, characterized in that: The modified zein delivery carrier is prepared by using a Na2CO3 solution or a Na2CO3 sacrificial template solution and then modified by phosphorylation.

2. The modified zein delivery carrier according to claim 1, characterized in that: Zein nanoparticles are hollow or solid structures.

3. The modified zein delivery carrier according to claim 1, characterized in that: Phosphorylation modification is carried out by sodium tripolyphosphate.

4. The modified zein delivery carrier according to claim 3, characterized in that: The preparation of Na2CO3 sacrificial template solution includes the following steps: mixing Na2CO3 aqueous solution with anhydrous ethanol.

5. The modified zein delivery carrier according to claim 4, characterized in that: The volume ratio of Na2CO3 aqueous solution to anhydrous ethanol is 1-5:9-5.

6. The method for preparing the modified zein delivery carrier according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) mixing a zein stock solution with a Na2CO3 sacrificial template solution, stirring to obtain a mixed solution, mixing the mixed solution with ultrapure water, continuing to stir, and rotary evaporating to obtain zein nanoparticles with a hollow structure; Alternatively, a zein stock solution is mixed with a Na2CO3 solution, stirred to obtain a mixed solution, the mixed solution is mixed with ultrapure water, stirred continuously, and rotary evaporated to obtain zein nanoparticles with a solid structure; (2) Mix the sodium tripolyphosphate solution with the hollow or solid zein nanoparticle solution and stir.

7. The preparation method according to claim 6, characterized in that: In step (1), the concentration of the zein stock solution is 0.5-2.5% (w / v), and the volume ratio of the zein stock solution to the Na2CO3 solution or the Na2CO3 sacrificial template solution is 1:1-5.

8. The preparation method according to claim 6, characterized in that: In step (1), the stirring time is 2-10 min, the volume ratio of the mixed solution to ultrapure water is 1:1-5, the stirring time is continued for 10-30 min, the rotary evaporation temperature is 35-42° C., and the rotary evaporation time is 25-40 min.

9. The preparation method according to claim 6, characterized in that: In step (2), the mass ratio of sodium tripolyphosphate to zein nanoparticles is 0.75-1.5:

1.

10. Use of the modified zein delivery carrier according to any one of claims 1 to 5 in the preparation of medicines or functional food ingredients.

Citation Information

Patent Citations

  • Nanoscale lactoferrin chitosan particle preparation method

    CN106177924A

  • Method for preparing hollow zein nanoparticles by adopting sodium bicarbonate template

    CN114887068A

  • Alcolamin composite hollow particle as well as preparation method and application thereof

    CN114948902A

  • Preparation method for stabilizing cinnamon bark essential oil Pickering emulsion by combining phosphorylated egg white protein colloidal particles and cellulose nanofibers

    CN115154362A

  • Chitosan-based edible film with nano-network structure as well as preparation method and application of chitosan-based edible film

    CN117946550A